Family coffee and good agricultural practices in Bom Sucesso - MG - Peixoto, Jaqueline Nicole Santos; Nunes, Márcio; Baliza, Danielle Pereira; Pereira, Sérgio Parreiras; Rosa, Beatriz Terezinha (Coffee Science - ISSN 1984-3909, 2017)
The objective in this study was to analyze the coffee familiar in the city of Bom Sucesso - MG, in relation to the adoption of Good Agricultural Practices, through the Cluster and discriminant analysis. It was held to recognize the current situation of the coffee familiar of the municipality with questionnaires structured type Survey in rural properties. It used the questionnaire to 26 family farmers associated with the Community Machado Association and the Association Our Lady of Badia. After the questionnaires, the results were tabulated and was performed multivariate statistical analysis of Cluster and later discriminant analysis. The Cluster analysis aims to group individuals (cases) with similar characteristics in terms of a set of selected variables that separated in this case the producers into two distinct groups. Already discriminant analysis showed the seven variables that most discriminate against another group, thus presenting the main differences between them. Group 1 producers have greater organizational characteristics than Group 2 for the adoption of Good Agricultural Practices. However, both the farmers Group 1 as Group 2 feature points that can be improved, which justifies the action planning and Technical Assistance and Rural Extension (ATER) for each group. Thus, it is expected that this study will assist in decision-making both by the local government as the family associations and farmers, so that this activity reach greater sustainability in the municipality.